Education, Health and Agricultural Expenditure and Their Impact on Rural Poverty in Nepal: A Time Series Data Analysis - Lamichhane, Dirgha Kumar; Shrestha, Sabina (Economic Journal of Nepal, 2011)
In this paper, seemingly unrelated regression analysis for finding relationship between public spending on agriculture, education, and health and rural poverty is examined by using public expenditure data of Nepal over 24 years. The data were drawn from Asian Development Bank and World Bank sources, which cover the period of 1981-2004. The paper derives the conclusion that the public spending on education and agriculture is significant and positively related to total factor productivity and hence related to improve the qualities of life, thereby reducing the poverty level. The comparative analysis of expenditure has found that the expenditure on education ( Eau = 0.24 N has greater impact on poverty than the spending on agriculture ( Eao 0 22 ): and health expenditure ( Doh = Qom )1.Key words: Health and agriculture; Rural poverty; Public spendingEconomic Journal of Nepal A Quarterly Publication of the Central Department of Economics T.U., Kirtipur Vol. 32, No. 1 January-March 2009, Issue No. 125Page: 24-34Uploaded date: 5 July 2011